Aspectos distributivos do regime de previdência dos servidores públicos - Leonardo Alves Rangel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper deals with the distributional aspects of Brazilian Civil Servant Pension System. It analyzes, in a counter factual way, the potential implications after the constitution of supplemental retirement pension fund for civil servants, at the light of what is predicted in the 41st Constitutional Amendment of year 2003. For the present analysis it is used data from the National Household Sample Survey of 2009. It used the Gini index decomposition method to analyze the distributional impacts associated with the scenarios constructed throughout the text. In summary, the imposition of a ceiling on the amount paid by Civil Servant Pension System has the potential to improve the distributional profile of public spending on pensions, but little impact on the distribution of total households personal income.
Keywords: H55; O15; D63; 330